Apology Response Strategies Performed by EFL Learners - Sri Waluyo (English Education Study Program, Faculty of Education and Teachers Training, Tidar Univer, 2017)
This research aims at scrutinizing apology response (AR) strategies performed by EFL learners in one of reputable universities in Indonesia. The research employed descriptive qualitative method in analyzing the data to figure out categories of the AR strategies performed and also to describe the factors which influenced the realization of AR strategies. Samples were selected with purposive sampling technique from 20 students in the final semester of English Department who were ranked as the Top 10 GPA in two available programs, i.e. English education and English literature. The technique in collecting the data used oral discourse completion task (DCT) that contained participants’ responses on the given apology situations. In general, the results showed that the four main AR strategies were performed by all the twenty participants with, specifically; 27 out of 33 extended strategies were detected. In detailed, the possible reasons which influence the realization of utterances produced by participants were significant roles of power, relation, setting of situations, and the degree of mistakes which correlated the participants with the addressees.Keywords: Apology Response Strategies; Interlanguage Pragmatics; EFL Learners.